Herpetología patagónica : XIV. Nuevos datos inmunológicos sobre iguánidos argentinos del grupo Liolaemus fitzingeri - Cei, José Miguel Alfredo María (1977)
Immunological tests by means of the precipitin reactions support nearby serological relationships between the Liolaemus (fitzingeri) melanops populations from Chubut and the populations belonging to the same morphological group found North of the Colorado River (Argentina). Cross-reactions between samples from Mendoza (Carrizal), San Juan (Bermejo), La Rioja (Baldecitos, Talampaya) provinces and samples from Chubut (Puerto Madryn) emphasize a very high percentage of identical specific antigens. Evolutive trends of this peculiar and widespread group of psammophilous iguanid lizards are briefly analyzed.